Effect of Oxide Compositions in the Portland Cement on Corrosion Behavior of Reinforcing Steel Embedded in Concrete - Keleştemur, Oğuzhan; Aksoy, Mustafa; Yıldız, Servet (My University, 2009)
In this study, corrosion behavior of reinforcing steel embedded in concrete samples obtained from CEM II /B-M 32.5 R Portland cement type which has been taken from various factories in order to determine effect of oxide compositions in the cement has been examined. For this purpose, the mixture ratio of concrete samples has been prepared according to ACI 211.1 and the same type and amount of materials have been used for the samples. The unique difference among samples was CEM II /B-M 32.5 R Portland cements on various producing center. The corrosion experiments were conducted in two stages. In the first stage, the corrosion potential of steels in the concrete was measured every day for a period of 90 days in accordance with ASTMC 876 standard. In the second stage, anodic and cathodic polarization values of these steels were obtained and then the corrosion currents were determined with the aid of cathodic polarization curves. As a result of this study, it was found that corrosion rate of reinforcing steel embedded in concrete affected with the change of oxide compositions in the cement.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Corrosion; Cement; Concrete; Reinforcing steel